LEARNING LEADERSHIP DAN EVALUATIVE THINKING SEBAGAI TRANSFORMASI PEMBELAJARAN BERKELANJUTAN PERSPEKTIF AL-QURAN - Fil Isnaeni (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This research discusses learning leadership and evaluative thinking which are important concepts and enable educational leaders to direct learning innovations based on reflection, data, and spiritual values. In the perspective of the Qur'an, evaluation does not only mean assessing learning outcomes, but also includes muhasabah (self-introspection), hikmah (wisdom), and islah (continuous improvement). This study aims to analyze the relevance of learning leadership and evaluative thinking to the transformation of Qur'anic education which is oriented towards the formation of reflective, critical, and moral human beings. This research uses a descriptive qualitative approach with a library research method that combines analysis of Qur'anic verses, classical and contemporary interpretations, and the results of scientific research in the field of Islamic education. The results of the study show that learning leadership is rooted in the Qur'anic values about the virtues of knowledge and faith (QS. Al-Mujadalah: 11), where the learning leader not only manages, but also becomes a facilitator and role model in the lifelong learning process. While evaluative thinking has a strong theological foundation in verses such as QS. Al-Hasyr: 18 on reflection on charity, QS. An-Nahl: 125 on wisdom, and QS. Thaha: 114 about the process of continuous learning.